PENGARUH MODEL COOPERATIVE LEARNING TIPE CONCEPT SENTENCE BERBANTUAN MEDIA PAPAN DESKRIPSI SERI KARTU BERGAMBAR (PADISIKABAR) TERHADAP KETERAMPILAN MENULIS KARANGAN DESKRIPSI SISWA KELAS III SD - Liya Sari Nawang Kusuma, Windi; Malihatul Hawa, Anni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem in this study is the low descriptive essay writing skills of third grade elementary school students. This study aims to determine the differences and effects of the Cooperative Learning model of the Concept Sentence type assisted by the Picture Card Series Description Board (PADISIKABAR) media on students' descriptive essay writing skills. This study uses a quantitative approach with the Quasi Experimental Design method using the Nonequivalent Control Group Design. The research sample was selected using a purposive sampling technique consisting of 52 students, namely 21 students in the experimental class and 31 students in the control class. Data were collected through tests, observations, and documentation, then analyzed using normality tests, homogeneity tests, Independent Samples t-tests, and simple linear regression tests. The results of the study showed a significant difference in descriptive essay writing skills between the experimental class and the control class based on the results of the Independent Samples t-test with a significance value of 0.000 <0.05, so that Ho was rejected and Ha was accepted. In addition, the results of the simple linear regression test also showed a significance value of 0.000 <0.05, so that Ho was rejected and Ha was accepted. Thus, it can be concluded that the Cooperative Learning Concept Sentence model, supported by PADISIKABAR media, significantly influenced the descriptive writing skills of third-grade elementary school students. Keywords: Concept Sentence, PADISIKABAR, Writing Skills.